The pacemaker’s role in maintaining cardiac physiology: A literature review - Fernandes, Isadora Silva; Campos, Ana Luisa Braga; Lima, Laura Rodrigues; Cunha, Marcello Augusto Soares; Nogueira, Nubia Santos; Silva, Paulo Henrique; Orsolin, Priscila Capelari; Thiago, Lucas Luis (Seven Editora, 2023)
Introduction: In people with heart problems associated with the malfunction of cardiac electrophysiology, it is necessary to use the pacemaker device, the equipment through artificial electrical pulses in the heart muscle of the right ventricle replaces the physiological pacemaker. Objective: To carry out a careful reading of the existing literature on the pacemaker and its importance in the maintenance of cardiac physiology and, thus, to contribute to future studies in the area and to improve the quality of life of people who need the aid of the device. Methodology: This is descriptive research of the integrative literature review type, which sought to answer the attributions of the pacemaker in the maintenance of cardiac physiology. The research was carried out through online access to the National Scientific Electronic Library Online (Scielo), Google Scholar and EBSCO Information Services databases, from August to October 2022. Results and discussion: Two important aspects of the literature were highlighted in the research : 1) The advancement of technology that enabled the development of better, less invasive and more accurate devices and the improvement of techniques for tracking heart problems - resulting in a decrease in the number of pacemaker implants and an increase in the number of implants other devices - in addition to pacemaker actuation techniques that improved the way the device works and consequently the patient’s physiological function; 2) The influence of the patient’s level of knowledge and psychological issues on the effectiveness of the implant, as these variables have the power to act as stimulators and/or inhibitors of acceptance of the surgical procedure and in the post-surgical adaptation, collaborating or not for the treatment effectiveness. Conclusion: The success of pacemaker implementation depends crucially on the techniques applied, the technological level of the equipment - these have been perfected and improved over time - and the emotional tranquility of the patients, which mainly reflects in the post-surgical period, that is, in the process of acceptance and adaptation to the pacemaker. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-134